The Integration of Artificial Intelligence in Project Management: A Systematic Literature Review of Emerging Trends and Challenges - Hashimzai, Irshad Ahmed; Mohammadi, Mohammad Qias (Universitas Pendidikan Nasional, 2024)
The integration of Artificial Intelligence (AI) in project management has emerged as a transformative approach, revolutionizing traditional practices by enhancing efficiency, decision-making, and risk management. Despite its potential, organizations face significant challenges, including high implementation costs, concerns over data privacy, and resistance to change, which hinder effective adoption. The purpose of this study is to explore emerging trends, key applications, and challenges of AI in project management, while also evaluating its impact on improving risk management, resource allocation, and decision-making in complex projects. The study employs a systematic literature review (SLR) methodology, adhering to the PRISMA protocol, to analyze peer-reviewed articles from MDPI, IEEE, Science Direct, and Emerald databases, published between 2018 and 2024. Keywords combined with Boolean operators were used to filter relevant studies, ensuring a balanced and focused selection of high-quality publications. The results reveal AI's capacity to proactively identify risks, adapt to dynamic project environments, and optimize resource allocation, ultimately enhancing decision-making efficiency and project outcomes. However, challenges such as implementation costs and resistance to organizational change remain critical barriers. The implications suggest that while AI significantly enhances project management, addressing these challenges is essential for broader adoption and scalability. This research concludes that AI is a game-changer in project management, offering insights into emerging trends and critical challenges. Future research should focus on developing scalable, cost-effective AI solutions to overcome adoption barriers, thereby extending the benefits of AI integration across diverse industries.